Manajemen Pembelajaran dalam Meningkatkan Prestasi Siswa di SMP Islam Al Ulum Terpadu Medan - Zahara Ahmad Fauzi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out how important learning management is in improving student achievement. Maximum learning management will have a maximum impact on student achievement. At the Al Ulum Integrated Islamic Middle School in Medan, learning management has not been implemented optimally. The aim of this research is to contribute to school leaders in learning management so that student achievement can increase. The type of research used in writing this thesis is qualitative with a descriptive approach. This research provides descriptive data in the form of manuscripts, interviews, field notes, personal documents, memos and other documents. The research subjects in this thesis are the principal, deputy principal for curriculum and teachers. This research data collection instrument uses observation, interview and documentation techniques. Data analysis techniques by reducing data, presenting data, verifying data. The results of this research indicate that the implementation of learning management in improving student achievement is still not optimal, both in terms of management and learning and how students' achievements are at school. For this reason, this research may be continued by interested parties.